Dual Antiplatelet or Dual Antithrombotic Therapy for Secondary Prevention in High-Risk Patients with Stable Coronary Artery Disease? - Sumaya, Wael; Geisler, Tobias; Kristensen, Steen D.; Storey, Robert F. (Thrombosis and Haemostasis, 2019)
Antithrombotic treatment is a key component of secondary prevention following acute coronary syndromes (ACS). Although dual antiplatelet therapy is standard therapy post-ACS, duration of treatment is the subject of ongoing debate. Prolonged dual antiplatelet therapy in high-risk patients with history of myocardial infarction reduced the risk of recurrent myocardial infarction, stroke or cardiovascular death. Similarly, in patients with stable coronary artery disease, two-thirds of whom had a history of myocardial infarction, dual antithrombotic therapy with very-low-dose rivaroxaban and aspirin also resulted in improved ischaemic outcomes. In the absence of head-to-head comparison, choosing the most appropriate treatment strategy can be challenging, particularly when it comes to balancing the risks of ischaemia and bleeding. We aim to review the evidence for currently available antithrombotic treatments and provide a practical algorithm to aid the decision-making process.
Keywords: coronary artery disease; dual antiplatelet therapy; dual antithrombotic therapy; rivaroxaban; ticagrelor